Pulmonary Rehabilitation With Balance Training for Fall Reduction in Chronic Obstructive Pulmonary Disease: Protocol for a Randomized Controlled Trial - Beauchamp, Marla (2018)
BACKGROUND: Chronic obstructive pulmonary disease (COPD) is a leading cause of morbidity and mortality worldwide. A growing body of evidence shows that individuals with COPD have important deficits in balance control that may be associated with an increased risk of falls. Pulmonary rehabilitation (PR) is a key therapeutic intervention for individuals with COPD; however, current international guidelines do not include balance training and fall prevention strategies. OBJECTIVE: The primary aim of this trial is to determine the effects of PR with balance training compared to PR with no balance training on the 12-month rate of falls in individuals with COPD. Secondary aims are to determine the effects of the intervention on balance, balance confidence, and functional lower body strength, and to estimate the cost-effectiveness of the program. METHODS: A total of 400 individuals from nine PR centers across Canada, Europe, and Australia will be recruited to participate in a randomized controlled trial. Individuals with COPD who have a self-reported decline in balance, a fall in the last 2 years, or recent near fall will be randomly assigned to an intervention or control group. The intervention group will undergo tailored balance training in addition to PR and will receive a personalized home-based balance program. The control group will receive usual PR and a home program that does not include balance training. All participants will receive monthly phone calls to provide support and collect health care utilization and loss of productivity data. Both groups will receive home visits at 3, 6, and 9 months to ensure proper technique and progression of home exercise programs. The primary outcome will be incidence of falls at 12-month follow-up. Falls will be measured using a standardized definition and recorded using monthly self-report fall diary calendars. Participants will be asked to record falls and time spent performing their home exercise program on the fall diary calendars. Completed calendars will be returned to the research centers in prepaid envelopes each month. Secondary measures collected by a blinded assessor at baseline (pre-PR), post-PR, and 12-month follow-up will include clinical measures of balance, balance confidence, functional lower body strength, and health status. The cost-effectiveness of the intervention group compared with the control group will be evaluated using the incremental cost per number of falls averted and the incremental cost per quality-adjusted life years gained. RESULTS: Recruitment for the study began in January 2017 and is anticipated to be complete by December 2019. Results are expected to be available in 2020. CONCLUSIONS: Findings from this study will improve our understanding of the effectiveness and resource uses of tailored balance training for reducing falls in individuals with COPD. If effective, the intervention represents an opportunity to inform international guidelines and health policy for PR in individuals with COPD who are at risk of falling.